2017
DOI: 10.1007/s40618-017-0712-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clinical efficacy and economic value in Basalin- and Lantus-treated patients with type 2 diabetes using continuous glucose monitoring system

Abstract: Glargine-Basalin is non-inferior in clinical efficacy compared to glargine-Lantus. In view of the large difference in the cost of glargine-Basalin, it would be much more cost-effective for our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…In contrast to our findings, a recently published blinded crossover study showed non-inferiority in terms of mean blood glucose, glucose fluctuations and rates of hypoglycemia as measured by CGMS for Chinese outpatients with T2DM receiving Basalin or Lantus 16 . Although patients in this previous study had a similar mean age, BMI and duration of T2DM as our study, there were several important differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, a recently published blinded crossover study showed non-inferiority in terms of mean blood glucose, glucose fluctuations and rates of hypoglycemia as measured by CGMS for Chinese outpatients with T2DM receiving Basalin or Lantus 16 . Although patients in this previous study had a similar mean age, BMI and duration of T2DM as our study, there were several important differences.…”
Section: Discussioncontrasting
confidence: 99%
“…However, while biosimilars are developed to be highly similar to originator therapies, due to the degree of natural variability inherent to biological drugs, which are produced using living organisms, and because of differences in manufacturing processes between products, they are not identical to the original therapy 15 . Results from a previous head-to-head study of Basalin and Lantus in Chinese people with T2DM showed equivalent glycemic control and safety, and a further crossover study in Chinese people with T2DM using a continuous glucose monitoring system (CGMS) reported non-inferiority of Basalin to Lantus for mean blood glucose, blood glucose fluctuations and rates of hypoglycemia 16 , 17 . However, other than these two previous reports, there are no further confirmatory studies in real-world clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ezelin (EZL) is an insulin glargine produced by Gan & Lee Pharmaceutical Ltd. or known in its home country as Basalin. 9,10 In Indonesia, EZL has obtained marketing authorization as biosimilar insulin glargine. EZL has proven its efficacy and safety in the previous clinical trial compared to the originator insulin glargine, which is Lantus (LAN).…”
Section: Introductionmentioning
confidence: 99%
“…EZL has proven its efficacy and safety in the previous clinical trial compared to the originator insulin glargine, which is Lantus (LAN). 9 To be able to replace its originator insulin product, the requirements that must be fulfilled by biological products are their similar efficacy, safety, and potential for immunogenicity. 7,11,12 Biological products, especially biosimilar, have the potential to cause an immunogenic response and may affect the efficacy and safety profile of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, CGM is primarily recommended to patients with type 1 diabetes and those with type 2 diabetes on intensive insulin therapy or who experience dramatic glycemic variability. When appropriate, CGM can also be used in clinical research as a valuable tool for assessing and guiding treatment Real‐time CGM is mainly applicable to the following patients or conditions: children and adolescents with type 1 diabetes whose HbA 1c less than 7%.…”
Section: Clinical Indications For Cgm Technologymentioning
confidence: 99%